The Efect Of Discovery Learning Natural Environment Exploration Model on Digestive System Materials Towards Critical Thinking and Science Process Skills - Dyah Siti Rohani; Siti Alimah (Universitas Negeri Semarang, 2024)
Basic competence in digestive system material requires critical thinking skills, facts in the field students' critical thinking skills still need to be optimized. The ability to think critically is able to encourage students to find concepts and practice science process skills. The purpose of the study was to examine the effect of the Discovery Learning Natural Environment Exploration model on students' critical thinking and science process skills and determine the relationship between critical thinking skills and science process skills. This quantitative research used a pre-experiment one group pretest and posttest design. This study involved students of SMA N 1 Cawas Class XI MIPA with a research sample of 70 students. The data obtained are in the form of test results of critical thinking skills, science process skills and syntax implementation data. The N-gain results obtained increased critical thinking skills and science process skills at moderate levels, with N-gain scores of 0.7 and 0.67. The results of Wallis's crucial test obtained significance values of 0.001 and 0.04, meaning that the Discovery Learning Natural Environment Exploration model affects critical thinking skills and science process skills. The results of the Spearman correlation test obtained a coefficient value of 0.749 (strong). The conclusion of this study is that the Discovery Learning Natural Environment Exploration model is influential in improving students' critical thinking skills and science process skills, critical thinking skills are strongly correlated with science process skills.